Correlation between Humerus Length and Height in Medical Students at Jambi University - Naufal Adli Marvi; Attiya Istarini; Rita Halim; Rina Nofri Enis; Huntari Harahap (Journal of Medical Studies, 2025)
ABSTRACT Background: Anthropometry is essential in identifying biological profiles, including height. One of the most commonly used anthropometric data to estimate height is the length of the humerus bone. This study analyzes the correlation between humeral length and height among medical students at UNJA. Methods: This study is an analytical correlational study conducted cross-sectionally. The sample consisted of male and female students who met the inclusion criteria: active medical students at UNJA who were willing to participate by signing an informed consent form. The exclusion criteria included deformities, a history of injuries, or bone disabilities. The humeral length was measured using a measuring tape, and height was measured using a microtoise. Results: The study found a correlation coefficient between humeral length and height ranging from 0.660 to 0.788 (p < 0.001). The simple linear regression equation obtained showed a Standard Error of the Estimation (SEE) ranging from 3.802 to 4.912 (p < 0.001). Conclusion: A strong positive correlation exists between humerus length and height, indicating that height can be estimated by measuring humerus length and applying it to the simple linear regression equation. Keywords: Anthropometry; Humeral length; Height; Regression equation